'It's very complicated': Perspectives and beliefs of newly graduated physiotherapists about the biopsychosocial model for treating people experiencing non-specific low back pain in Brazil. (July 2019) - França, Andressa Alves; Santos, Vagner dos; Filho, Reginaldo Lordelo; Pires, Kênia Fonseca; Lagoa, Karina Ferreira; Martins, Wagner Rodrigues
Abstract: Non-specific low back pain is a common complaint frequently presented by patients and this complex clinical condition has challenged the biomedical model. The Biopsychosocial (BPS) model is recognized as an option for better guidance and patient management. However, physiotherapy training is based on the biomedical perspective, added to which, in clinical practice the applicability of the BPS model is a challenge for many professionals. In this article, we explore the feelings, beliefs, and attitudes of newly trained physiotherapists about using the BPS model to treat people with non-specific low back pain. It also aims to understand to what extent these physiotherapists are willing and prepared to use this model. Method: A qualitative phenomenological research was carried out in the Brazilian federal capital. A set of criteria was used to select 10 physiotherapists. The data were collected through semi-structured interviews and analyzed using five steps: familiarization, identification, indexation, mapping, and interpretation. Results: We identified one theme and three categories. The theme 'a practitioner physiotherapist can consider BPS aspects, but it is not necessary in his/her role to approach them' explains a shared belief about the use of BPS. The theme is better understood when looking at the three categories that explore and exemplify key elements of the theme: (i) understanding the BPS model and its relation to non-specific low back pain; (ii) the role of practitioner physiotherapists regarding the BPS model; and (iii) barriers: from undergraduate training to clinical settings. Highlights: The biopsychosocial model is an option for better patient orientation and management. Training in physiotherapy remains based on the biomedical perspective. What are the beliefs about newly trained physiotherapists about using the model?